2022
DOI: 10.1002/alr.23009
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic endonasal resection of pediatric craniopharyngiomas

Abstract: Background: Craniopharyngiomas have traditionally been treated via open transcranial approaches. More recent, endoscopic endonasal approaches have been increasingly used; however, there has been limited evaluation of long-term outcomes for this approach. Methods: A retrospective review was performed to analyze patients with pediatric craniopharyngioma undergoing endonasal endoscopic resection from 2012 to 2020. Demographic information, clinicopathologic factors, and outcomes including follow-up and recurrences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In the current study, we observed that pre-existing endocrine dysfunction appears to be permanent, and in fewer than 5% of patients with pre-existing endocrine dysfunction, endocrine function improved after surgery (data not shown). These findings are consistent with those reported by Patel et al [ 29 ]. Additionally, we found that EETS can reduce the incidence of new hormonal deficits following surgery compared to TC, and the protective effects of EETS seem not to act on anterior pituitary function but only on posterior pituitary function and hypopituitarism ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, we observed that pre-existing endocrine dysfunction appears to be permanent, and in fewer than 5% of patients with pre-existing endocrine dysfunction, endocrine function improved after surgery (data not shown). These findings are consistent with those reported by Patel et al [ 29 ]. Additionally, we found that EETS can reduce the incidence of new hormonal deficits following surgery compared to TC, and the protective effects of EETS seem not to act on anterior pituitary function but only on posterior pituitary function and hypopituitarism ( Figure 3 ).…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, permanent DI was found at a higher rate in patients with aggressive surgery than in patients with less aggressive surgery combined with radiotherapy [ 30 ]. However, our team also favors the same view as that of Patel [ 29 ] and Yamada [ 31 ]: GTR but not STR should be the surgical goal for the first surgical attempt because it can prolong the time to tumor recurrence and reduce the need for postoperative adjuvant therapy. Moreover, under the premise of the EETS method, GTR was accomplished with a high rate of improved HI, less new-onset posterior pituitary dysfunction ( Figure 3 ), and less new-onset hypopituitarism ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, use of EEA in pediatric patients is becoming increasingly common as studies show effective tumor control with experienced surgeons [38]. Furthermore, recent studies have shown that for appropriately located tumors in children, EEA can achieve similar rates of resection and recurrence compared to TCA, with mixed results as to the superior method for preserving hypothalamic–pituitary function [39,40 ▪ ]. TCA is still utilized but is generally reserved for large tumors with lateral extension [38].…”
Section: Surgical Managementmentioning
confidence: 99%